Infestation of introduced raccoons (Procyon lotor) with indigenous ixodid ticks on the Miura Peninsula, Kanagawa Prefecture, Japan - Doi, Kandai; Kato, Takuya; Hayama, Shin-ichi (International journal for parasitology. Parasites and wildlife, 2018)
Since the raccoon (Procyon lotor) was introduced to Japan, studies have established that they are infested with native Japanese tick species. However, the quantity of ticks infesting raccoons is unknown. We conducted a survey of ticks on invasive raccoons captured on the Miura Peninsula, Kanagawa Prefecture, Japan, from April 2015 through June 2016 to determine the species of ticks and to quantify the intensity of tick infestation in order to obtain basal information related to the ecology of host–parasite relationships among indigenous tick species and an alien mammalian species. We collected and identified 15,931 ticks of two genera and six species, namely, Haemaphysalis flava, H. megaspinosa, H. longicornis, H. japonica, Ixodes ovatus, and I. tanuki, from 100 out of 115 raccoons. The dominant tick species was H. flava (96.8%) and individuals were mainly adults. Seasonal patterns of infestation intensity of adults and nymphs peaked in the autumn and winter and decreasing in the late spring and summer, May to August, while larvae peaked in August. Our results indicated that host–parasite relationships between invasive raccoons and Japanese tick species, especially H. flava, were established in Kanagawa Prefecture. The ticks infest invasive raccoons for their blood-meal and also for overwintering. The results of this study extend our understanding of the ecology of tick-borne diseases. [Display omitted] •All developmental stages of Haemaphysalis flava infested feral raccoons.•Adults H. flava was dominant tick infested raccoons.•The peak of tick infestation raccoons was in late autumn and winter.•Adults and nymphal H. flava use raccoons for blood-meal and overwintering.